The dawn of two dawns: The mythical, royal and temporal implications of dawn for Psalms 108 and 110 - Sutton, Lodewyk (HTS teologiese studies, 2017)
Shachar is identified primarily as a primary noun that is translated as ‘dawn’ within the Hebrew Bible, yet one must not ignore its mythical dimension. Within the Davidic trilogy Psalms 108–110, Shachar takes on an important function, concerning the unity and the message of the trilogy within Book V (Pss 107–150) of the Book of Psalms. A process of restoration (of honour and identity) and hope is announced within Psalm 108 and started within Psalm 110 for Israel after a time of war and exile. This is demonstrated through the mythical, royal and temporal dimensions of Shachar as two dawns within Psalm 108:3 and Psalm 110:3.